Peran Brand Love Memediasi Pengaruh Brand Experience dan Brand Image Terhadap Brand Loyalty: Studi pada Konsumen Sepatu Olahraga Adidas di Kota Denpasar - Putu Devira Wulandari; Shine Pintor Siolemba Patiro; Arthur Sitaniapessy (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study investigates the role of brand love as a mediator in the relationship between brand experience, brand image, and brand institutionalization among Adidas Sports Shoes consumers in Denpasar City. The concept of brand love is increasingly recognized as a critical factor in building customer loyalty, as it establishes a deep emotional connection between consumers and brands. This study uses a survey approach, collecting data from 200 Adidas Sports Shoes consumers in Denpasar City. The results show that brand experience and brand image have a significant positive impact on brand institutionalization, and brand love plays a mediator in this relationship. Specifically, the results show that brand experience influences brand image, which then influences brand love, and ultimately influences higher brand institutionalization. This study contributes to the existing literature by highlighting the critical role of brand love in connecting brand experience and brand institutionalization, as well as providing incidents for marketers to develop effective strategies to build brand love among their customers.